THE ROLE OF NURSES IN PREVENTING AND CONTROLLING COMPLICATIONS IN ONCOLOGICAL PATIENTS: A LITERATURE REVIEW (REMUNOM, 2025)
The role of nurses in oncology care is fundamental for the prevention and control of complications, considering the specificities of this health condition. The literature highlights that cancer patients are subject to the consequences arising from the disease itself and from treatments, such as chemotherapy, radiotherapy and surgeries, which can generate severe adverse effects, such as infections, hematological alterations, malnutrition, fatigue and emotional complications. Based on this information, this work is based on the form of a bibliographic review, exploring studies and scientific evidence that address the role of nurses in the prevention and control of complications in cancer patients, with the objective of identifying effective practices, challenges faced and strategies that can contribute to improving the care and quality of life of these patients. Thus, we know that nurses play a central role in surveillance, early identification of complications and implementation of preventive and therapeutic measures. Prevention actions include continuous monitoring of signs and symptoms, encouraging adherence to treatment, health education on home care and healthy habits, and promoting self-care. Furthermore, the management of adverse effects requires the application of specific care protocols, such as administration of medications to control nausea and pain management, care of catheters and venous accesses, and nutritional guidance to avoid malnutrition. Thus, the nurse also acts as a mediator, offering psychological support and integrating a multidisciplinary team to promote the patient's overall well-being. Through a holistic and evidence-based approach, the nurse's role is necessary to reduce risks, control complications and improve clinical trials and the quality of life of cancer patients, reinforcing the essential nature of nursing in the oncological context.